"Drop Turkey from NATO now": Construction of Anti-Türkiye Discourse in the U.S. Public Opinion - TURGUT, Hasan; ÇAKIR, Ali (Kastamonu University, 2023)
After the outbreak of the Ukraine-Russia War, Sweden and Finland abandoned their neutrality policies and announced that they would apply for NATO membership. Türkiye declared that it would veto their membership applications, stating that these two countries supported terrorist organizations. This situation alarmed the European member countries of NATO and the United States, and it was stated that Türkiye's veto would cause a rift in the NATO alliance and jeopardize European security. This study analyzes reader comments in the three leading U.S. newspapers: The New York Times, The Washington Post, and The Wall Street Journal. The study was limited to the reader's comments on news about Türkiye's veto between May 19, 2022, when Türkiye announced its objection to Sweden and Finland's NATO membership applications, and June 30, 2022, when the crisis was resolved. The study applies an eclectic methodology and employs a corpus-assisted discourse analysis method. The themes, strategies, and linguistic practices through which Türkiye and Turkish identities are discursively constructed were analyzed. As a result of the analysis, it was concluded that Türkiye's announcement to veto Sweden’s and Finland's membership applications to NATO has fed the anti-Turkish sentiment that dominates U.S. public opinion, especially in the context of Türkiye-U.S. relations that reached a breaking point after 2016. Moreover, it is argued that anti-Turkish sentiment is constructed through “traditional” discourse themes such as the stereotype of the “bad Turk” and Islamophobia, as well as discourse themes that establish the identification of President Erdoğan and Türkiye.
Keywords: Communication and Media Studies; İletişim ve Medya Çalışmaları; Türkiye; NATO; ABD Kamuoyu; Derlembilim Söylem Analizi; Ukrayna-Rusya Savaşı; Türkiye; NATO; US Public; Corpus-assisted Discourse Analysis; Ukraine-Russia War; 5. Gender equality; 4. Education; 8. Economic growth; 10. No inequality; 16. Peace & justice